A Stem Cell Surge During Thyroid Regeneration - Ma, Risheng; Morshed, Syed A.; Latif, Rauf; Davies, Terry F. (Frontiers in Endocrinology, 2021)
Background: Many tissues, including the thyroid, contain resident (adult) stem cells that are responsible for regeneration and repair after injury. The mechanisms of thyroid regeneration and the role of thyroid stem cells and thyroid progenitor cells in this process are not well understood. We have now used a new mouse thyroid injury model to gain insight into this phenomenon. Methods: Tamoxifen induced TPO-Cre mice (TPOCreER2) were crossed with inducible Diphtheria Toxin Receptor homozygous mice (ROSA26iDTR) to give rise to TPOCreER2/iDTR mice, allowing for the Cre-mediated expression of the DTR and rendering TPO expressing thyroid cells highly sensitive to diphtheria toxin (DT). This model of TPOCreER2/iDTR mice allowed us to study the repair/regeneration of thyroid follicles after diphtheria toxin induced thyroid damage by measuring serum thyroid hormones and cell fate. Results: In TPOCreER2/iDTR double transgenic mice we observed severe thyroid damage as early as 2 weeks after initiating intraperitoneal DT injections. There was marked thyroid tissue apoptosis and a ~50 % drop in serum T4 levels (from 5.86 to 2.43ug/dl) and a corresponding increase in serum TSH (from 0.18 to 8.39ng/dl). In addition, there was a ~50% decrease in transcription of thyroid specific genes (thyroglobulin, TSH receptor and sodium-iodide symporter). After suspending the DT administration, the thyroid rapidly recovered over a 4 week period during which we observed a transient surge in stem cell marker expression (including Oct4, Nanog, Sox2 and Rex1). In addition, cells immunostaining with stem cell markers Oct4 and Ssea-1 were found in clusters around new thyroid follicles in TPOCreER2/iDTR double transgenic mice. Furthermore, the presence of clusters of thyroid progenitor cells was also identified by Pax8 staining of thyroglobulin negative cells. This recovery of the injured gland was followed by a rapid and sequential restoration of thyroid function. Conclusion: These data demonstrate that a new model of thyroid cell damage induced by DT can be used to study the mobilization of resident adult stem cells. Furthermore, the model clearly demonstrates the involvement of both stem and progenitor cells in the in vivo regeneration of the thyroid after severe destruction.